The relevance of broadcasting regulation in the era of media convergence - Awanis Akalili (Journal of Social Studies (JSS), 2020)
The Broadcasting Law Number 32, 2002 regulates about broadcasting media in Indonesia. Technological development that brings the media convergence era, becomes one of the biggest challenge for the broadcasting regulation in this country. One of the form of media convergence is the convergence ownership, that is the ownership merger of media company as various platform under one company name. Media Nusantara Citra Tbk (MNC) is an example for this. Using library research method, this research analyze broadcasting regulation relevance of the Broadcasting Law Number 32, 2002 in the media convergence era, particularly convergence ownership implemented by MNC. The researcher found from this research that the Broadcasting Law Number 32, 2002 does not yet include media convergence issue, in which convergence ownership is included. This law depicted only the limitation of media ownership, where the limitation itself is not explained in detail. With the unclear convergence ownership regulation, in this case, MNC could be freely expanding its business network of broadcasting media (TV and radio), printed media, even online media. Moreover, MNC also has the control to three of Indonesia's biggest TV broadcasting media, namely RCTI, Global TV and MNC TV. This urges Indonesia's government to act immediately by revising the regulation of media broadcasting to be adaptable to the era of media convergence, specifically to convergence ownership issue.